Cadena de valor de plantas aromáticas, medicinales y condimentarias. Una industria en pleno desarrollo. Retos y oportunidades en el panorama colombiano - Grande Tovar, Carlos David (Señales, 2015)
This book discusses some aspects related to production (planting, harvesting and harvesting), primary processing (post-harvest conditioning operations for conservation and suitability for further processing into derivatives such as oils, extracts, active ingredients, etc.), secondary processing (packaging, packing and storage operations) and marketing, all through the analysis of market behavior in Colombia and the world. The purpose is to introduce the student to the basic aspects related to the growing industry of aromatic, medicinal and condimentary plants in Colombia.